Additive manufacturing for designers : a primer - Elliott, Amy; Waters, Cynthia (SAE International, 2019)
Discusses the topics needed for designers to gain a holistic understanding of the micro and macro components of the world of AM, or 3D printing. The book offers a brief history of AM, a discussion of the difference between rapid prototyping and AM, and standard terminology for each type of AM technology. The role and impact of standards is also presented.
"An SAE Deep Dive."
Keywords: Additive manufacturing.; Three-dimensional printing.; Manufacturing processes -- Automation.; Materials -- Technological innovations.; elektronické knihy; electronic books